2019
DOI: 10.2147/tcrm.s195267
|View full text |Cite
|
Sign up to set email alerts
|

<p>Analgesia and sedation post-coronary artery bypass graft surgery: a review of the literature</p>

Abstract: This review aimed to study the role of analgesia and sedation after coronary artery bypass graft (CABG) surgery, regarding pain management, assisted respiration, overall postoperative health care, and hospitalization. Data were collected from Pubmed, Scopus, and Cochrane databases. The following terms were used for the search: “analgesia”, “sedation”, “coronary artery bypass grafting”, CABG”, and “opioids”. Articles between the years 1988 and 2018 were evaluated. Several opioid and non-opioid analgesics used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Currently, pharmacological treatments for anxiety and pain are well-developed in the ICU environment, where pain and fatigue are most commonly managed by opioid analgesics, propofol and benzodiazepines [14]. Pharmacological treatment could be considered efficient when the patient feels comfortable, with no adverse effects [15]. Yet, opioid analgesics (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, pharmacological treatments for anxiety and pain are well-developed in the ICU environment, where pain and fatigue are most commonly managed by opioid analgesics, propofol and benzodiazepines [14]. Pharmacological treatment could be considered efficient when the patient feels comfortable, with no adverse effects [15]. Yet, opioid analgesics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, opioid analgesics (e.g. morphine) often lead to respiratory sedation, hyperalgesia, depression, nausea, opioid-induced tolerance and dependence [15]. Benzodiazepines can be used in the short term but can lead to strong dependence, with important adverse effects: ataraxia, irritability, nervousness, depression and risk of suicide [16].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Because of the high intensity of pain and subsequent high stress and serious hemodynamic complications, the management of pain after heart surgery has always been a major concern for physicians and nurses. [ 2 ] To control postoperative pain, pharmacological and non-pharmacological treatments (such as acupuncture, massage, Transcutaneous Electrical Nerve Stimulation [TENS], and heat or cold packs) might be considered. Treatment interventions that are commonly used include opioids, paracetamol, Nonsteroidal Anti-Inflammatory Drugs (NSAIDs), and more recently anticonvulsants.…”
Section: Introductionmentioning
confidence: 99%
“…However, pain intensity is among the multifactorial problems in patients after CABG, which is affected by a number of uncontrollable factors such as age, gender, health status, and type of intervention. [ 2 ] Moreover, results of a study in 2018 showed that environmental factors such as noise, light, and temperature are stressors for patients admitted to the Intensive Care Unit (ICU). [ 3 ] Kryter,[ 4 ] in his book “Effects of Noise in Man,” proposed that noise stimulates the reticular nervous system, leading to arousal responses of the central nervous system which tends to pain perception in different organs of the body.…”
Section: Introductionmentioning
confidence: 99%
“…(1)(2)(3). actually, there are too many drugs used in postoperative period for reducing pain: nSaiD, ketamine, Dexmedetomidine, magnesium, local anesthetics, gabapentin, epidural anesthesia, (4). Major role in cardiac anesthesia plays high doses of opioids, but can lead to prolonged sedation and delay in tracheal extubation.…”
Section: Introductionmentioning
confidence: 99%